Arginase and arginine in diagnostics of patients with colorectal cancer and patients with colorectal cancer liver metastases - Mielczarek-Puta, Magdalena; Graboń, Wojciech; Chrzanowska, Alicja; Barańczyk-Kuźma, Anna (Contemporary Oncology/Współczesna Onkologia, 2008)
Aim of the study: Determination and comparison of arginase activity and L-arginine level in blood serum of patients with colorectal cancer and colorectal cancer liver metastases, and an assessment of diagnostic usefulness of studied parameters. Material and methods: Blood samples were taken from all patients just before their surgery arginase activity and L-arginine level were determined spectrophotometrically. Results: Serum arginase activity in patients with colorectal cancer was over 3-fold higher compared to healthy blood donors and as much as 6-fold higher in those with colorectal cancer liver metastases. An increased arginase activity was associated with a 2-fold increase in arginine level in both patients’ groups. Both parameters showed high sensitivity - for the group with primary colorectal cancer it was 83% and 90% for arginase and L-arginine, respectively, and for the group with colorectal cancer liver metastasis 81% for arginase and 96% for L-arginine. Conclusions: determination of arginase activity as well as L-arginine concentration in blood serum may be useful in diagnosis of patients with colorectal cancer and colorectal cancer liver metastases. Concomitant evaluation of both parameters increases the diagnostic value of arginase determination itself, however it does not allow the differential diagnosis between primary and metastatic colorectal cancer.